Potential use of groundnut shell ash in sustainable stabilized earth blocks - Sathiparan, N.; Anburuvel, A.; Virgin Vinusha, S.; Vithurshan, P.A. (Elsevier, 2023)
Cement is generally used as a stabilizer for the production of stabilized earth blocks, which has become more popular due to its cost-effectiveness and eco-friendliness. However, cement is infamous for being environmentally unfriendly because of higher energy use during its production and significant emissions of CO2 cum other greenhouse gases. Cement alternatives have so attracted a lot of interest in recent years. Groundnut shell ash (GSA) is one of the potential waste materials to be used for cement replacement. This article includes an experimental investigation on the properties of stabilized earth blocks using GSA as a cement substitute. The percentage by mass of the total binder in the stabilized earth block that has replaced with GSA content is 0%, 10%, 20%, 30%, and 40%. The experiments on stabilized earth blocks investigate the physical, mechanical, durability properties and thermal performance as well as cost-effectiveness and eco-benefit analysis. Results show that, even though the strength of stabilized earth blocks decreases with GSA content, it improves the thermal performance, lowers the production cost and reduces the CO2 emission and embodied energy. The conclusions of the study suggest that stabilized earth blocks based on GSA have some promise for significantly reducing the amount of cement needed in the building sector.
Keywords: Masonry; Stabilized earth block Cement; Groundnut shell ash; Sustainability